Feasting and fasting : the history and ethics of Jewish food - Gross, Aaron S.; Myers, Jody Elizabeth, 1954-; Rosenblum, Jordan, 1979-; Diner, Hasia; Foer, Jonathan Safran (New York University Press, 2019)
"Judaism is a religion that is enthusiastic about food. Jewish holidays are inevitably celebrated through eating particular foods, or around fasting and then eating particular foods. Through fasting, feasting, dining, and noshing, food infuses the rich traditions of Judaism into daily life. What do the complicated laws of kosher food mean to Jews? How does food in Jewish bellies shape the hearts and minds of Jews? What does the Jewish relationship with food teach us about Christianity, Islam, and religion itself? Can food shape the future of Judaism? Feasting and Fasting explores questions like these to offer an expansive look at how Judaism and food have been intertwined, both historically and today. It also grapples with the charged ethical debates about how food choices reflect competing Jewish values about community, animals, the natural world and the very meaning of being human. Encompassing historical, ethnographic, and theoretical viewpoints, and including contributions dedicated to the religious dimensions of foods including garlic, Crisco, peanut oil, and wine, the volume advances the state of both Jewish studies and religious studies scholarship on food. Bookended with a foreword by the Jewish historian Hasia Diner and an epilogue by the novelist and food activist Jonathan Safran Foer, Feasting and Fasting provides a resource for anyone who hungers to understand how food and religion intersect."--